Training on Using Canva and Google Classroom for Prospective Teachers in Implementing Interactive Learning at STAIN Mandailing Natal - Amru Abdul Wadud; Owi Ali Nurdin Malayu; Rony Hamdani Siregar; Zulhimma Zulhimma (World Journal of Islamic Learning and Teaching, 2025)
The development of digital technology has brought significant changes to learning practices at various levels of education. This situation requires prospective teachers to have technology-based pedagogical competencies to be able to create innovative and interactive learning. Canva and Google Classroom are digital platforms that can be utilized as learning support media because they are easily accessible and have features relevant to educational needs. This article aims to describe the implementation and results of training on the use of Canva and Google Classroom for prospective teachers at STAIN Mandailing Natal. This activity uses a participatory training approach by actively involving prospective teachers. The training was carried out through interactive lectures, demonstrations, hands-on practice, and ongoing mentoring. The material covered technology-based interactive learning, the use of Canva as an educational visual medium, and the use of Google Classroom for digital classroom management. Participants were guided to produce digital teaching materials and virtual classes independently, accompanied by mentoring in overcoming technical and pedagogical obstacles. Evaluation was carried out through active observation, assessment of practical results, and reflection on the training experience. The results of the activity showed an increase in participants' understanding and skills in designing visual learning media and managing digital classrooms effectively. This training made a positive contribution in developing prospective teachers who are adaptive to technological developments and able to implement interactive learning according to the demands of 21st-century education.